Lansoprazole induces sensitivity to suboptimal doses of paclitaxel in human melanoma. Issue 2 (28th January 2015) - Azzarito, Tommaso; Venturi, Giulietta; Cesolini, Albino; Fais, Stefano
Abstract: Tumor acidity is now considered an important determinant of drug-resistance and tumor progression, and anti-acidic approaches, such as Proton Pump inhibitors (PPIs), have demonstrated promising antitumor and chemo-sensitizing efficacy. The main purpose of the present study was to evaluate the possible PPI-induced sensitization of human melanoma cells to Paclitaxel (PTX). Our results show that PTX and the PPI Lansoprazole (LAN) combination was extremely efficient against metastatic melanoma cells, as compared to the single treatments, both in vitro and in vivo . We also showed that acidity plays an important role on the anti-tumor activity of these drugs, being detrimental for PTX activity, while crucial for the synergistic effect of PTX following pretreatment with LAN, due to its nature of pro-drug needing protonation for a full activation. We obtained straightforward results in a human melanoma xenograft model combining well tolerated LAN doses with suboptimal and poorly toxic doses of PTX. With this study we provide a clear evidence that the PPI LAN may be included in new combined therapy of human melanoma together with low doses of PTX.